Development and Diversification: Sustainability Strategies for a Costa Rican Fishing Cooperative - Charles, Anthony T. (1994)
"Successful" fishery development can be defined as the simultaneous achievement of ecological, socioeconomic, community and institutional sustainability. This paper incorporates these sustainability elements within an integrated framework, which is applied in a case study of Puerto Thiel, a fishing community in the Gulf of Nicoya on Costa Rica´s Pacific coast. The economic performance of the local fishing cooperative is analysed, and experiences with economic diversification are reviewed. We highlight the importance, especially in heavily exploited fisheries, of policies that simultaneously pursue development (10 increase local socioeconomic and community fishery benefits within resource limitations) and economic diversification (to lessen the impact of fishery management restrictions by creating non-fishery employment alternatives).